Life Cycle Assessment (LCA) of Biodiesel Production from Coconut Pulp Using In-Situ Transesterification with Microwave Energy - Daya Wulandari; Riztamala Diana; Godlove Elioth Kiswaga; Leila Utarina; Devina Sanchia Samosir; Marisa Tri Octavia (Justek : Jurnal Sains dan Teknologi, 2026)
Coconut pulps are solid waste from coconut processing that has had its coconut milk extracted, with a remaining oil content of around 12.2–15.9%. The processing of coconut pulp is not yet optimal, and this waste has the potential to be utilized as renewable energy in the form of biodiesel. Biodiesel is produced through an in-situ transesterification process assisted by microwave energy. This study aims to identify the potential environmental impacts of biodiesel production from coconut pulp as fuel. A Life Cycle Assessment (LCA) was conducted using the cradle-to-gate approach with the SimaPro ver. 9.4.0.3 data processing application and a database similar to the eco-invent database. The environmental impact assessment was analyzed using the EF 3.0 Method (adapted) V1.03 / EF 3.0 normalization and weighting set. The results show that among the stages of the biodiesel production process, the transportation of raw materials and supporting materials has the greatest impact on climate change compared to other stages. The transportation stage contributed 78.19 kg CO₂-eq out of a total of 204.35 kg CO₂-eq in the climate change category and dominated energy resource use at 1108.14 MJ out of a total of 1742.17 MJ. In addition, the preparation stage also contributed significantly to climate change, with emissions reaching 56.21 kg CO₂-eq. The large contribution from the transportation stage was mainly caused by exhaust gas emissions from vehicles used to transport raw materials and supporting materials. Based on the LCA results, environmental performance improvements or continuous improvements that can be implemented include optimizing logistics, regulating fuel use, selecting the nearest sources of raw materials, and improving energy efficiency during the preparation stage to support more sustainable biodiesel production from coconut pulp.